Health extension workers' level of job satisfaction in western Hararghe Zone, eastern Ethiopia: an institutional-based cross-sectional study - Aman, Kemal; Gobena, Tesfaye; Hawulte, Behailu; Maruta, Melat B.; Debella, Adera; Eyeberu, Addis; Abrahim, Rudwan; Wakjira, Olifan; Mussa, Ibsa (Frontiers in Health Services, 2024)
Background There is a concern that job dissatisfaction among health extension workers (HEWs) reduces the benefit of investment in the execution of health extension programs. Hence, the purpose of this study was to explore the level of job satisfaction and factors affecting it among the HEWs in the West Hararghe Zone, Oromia Regional State, eastern Ethiopia. Method An institutional-based cross-sectional study was conducted among 416 randomly selected health extension workers from 20 September 2020 to 20 October 2020. A pretested, structured questionnaire was used to collect the data. STATA 14.2 was used for data analysis. Bivariable and multivariable binary logistic regression analyses were also performed. Statistical significance was set at P < 0.05. Results The overall level of satisfaction of health extension workers was 51.8% [95% confidence interval (CI): 46.97%, 56.6%]. Earning more than 5,260 ETB as salary [adjusted odds ratio (AOR) = 1.69, 95% CI: 1.01, 2.85], working more than 10 km from the district town (AOR = 1.59, 95% CI: 1.01, 2.53), receiving supportive supervision (AOR = 1.64, 95% CI: 1.06, 2.55), and not living with parents (AOR = 1.94, 95% CI: 1.24, 3.04) were significantly associated factors with HEW job satisfaction. Conclusion Nearly half of the health extension workers were dissatisfied with their jobs. Supportive supervision, compensation, distance, and parental home location were all predictors of job satisfaction. It is critical to establish intervention tactics that may satisfy and motivate HEWs to expand health coverage, strengthen health extension programs, and improve service delivery.